Spectral signatures of mirror movements in the sensori‐motor connectivity in kallmann syndrome. Issue 1 (30th September 2017) - Manara, Renzo; Di Nardo, Federica; Salvalaggio, Alessandro; Sinisi, Antonio Agostino; Bonanni, Guglielmo; Palumbo, Vincenzo; Cantone, Elena; Brunetti, Arturo; Di Salle, Francesco; D'errico, Arianna; Elefante, Andrea; Esposito, Fabrizio
Abstract: Mirror movements (MM) might be observed in congenital and acquired neurodegenerative conditions but their anatomic‐functional underpinnings are still largely elusive. This study investigated the spectral changes of resting‐state functional connectivity in Kallmann Syndrome (hypogonadotropic hypogonadism with hypo/anosmia with or without congenital MM) searching for insights into the phenomenon of MM. Forty‐four Kallmann syndrome patients (21 with MM) and 24 healthy control subjects underwent task (finger tapping) and resting‐state functional MRI. The spatial pattern of task‐related activations was used to mask regions and select putative motor networks in a spatially independent component analysis of resting‐state signals. For each resting‐state independent component time‐course power spectrum, we extracted the relative contribution of four separate bands: slow‐5 (0.01–0.027 Hz), slow‐4 (0.027–0.073 Hz), slow‐3 (0.073–0.198 Hz), slow‐2 (0.198–0.25 Hz), and analyzed the variance between groups. For the sensorimotor network, the analysis revealed a significant group by frequency interaction ( P = 0.002) pointing to a frequency shift in the spectral content among subgroups with lower slow‐5 band and higher slow‐3 band contribution in Kallmann patients with MM versus controls ( P = 0.028) and with lower slow‐5 band contribution between patients with and without MM ( P = 0.057). In specific regions, as obtained from hand motor activation task analysis, spectral analyses demonstrated a lower slow‐5 band contribution in Kallmann patients with MM versus both controls and patients without MM ( P < 0.05). In Kallmann syndrome, the peculiar phenomenon of bimanual synkinesis is associated at rest with regionally and spectrally selective functional connectivity changes pointing to a distinctive cortical and subcortical functional reorganization. Hum Brain Mapp 39:42–53, 2018 . ©2017 Wiley Periodicals, Inc.